2016
DOI: 10.1038/oncsis.2016.53
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptomic analysis reveals the oncogenic fusion protein PAX3-FOXO1 globally alters mRNA and miRNA to enhance myoblast invasion

Abstract: Rhabdomyosarcoma, one of the most common childhood sarcomas, is comprised of two main subtypes, embryonal and alveolar (ARMS). ARMS, the more aggressive subtype, is primarily characterized by the t(2;13)(p35;p14) chromosomal translocation, which fuses two transcription factors, PAX3 and FOXO1 to generate the oncogenic fusion protein PAX3-FOXO1. Patients with PAX3-FOXO1-postitive tumors have a poor prognosis, in part due to the enhanced local invasive capacity of these cells, which leads to the increased metast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 51 publications
2
12
0
Order By: Relevance
“…The data from the GSE44667 database showed high methylation levels of the PAX3 gene in the placenta of patients with PE [10]. This result is consistent with the low expression of PAX3 in the same patients, which was identified in our previous study [3]. Therefore, this evidence suggest that high methylation levels of PAX3 gene are an important cause of low expression.…”
Section: Introductionsupporting
confidence: 86%
See 2 more Smart Citations
“…The data from the GSE44667 database showed high methylation levels of the PAX3 gene in the placenta of patients with PE [10]. This result is consistent with the low expression of PAX3 in the same patients, which was identified in our previous study [3]. Therefore, this evidence suggest that high methylation levels of PAX3 gene are an important cause of low expression.…”
Section: Introductionsupporting
confidence: 86%
“…However, PAX3 is abnormally down-regulated in the placenta of PE patients, and a low expression of PAX3 is associated with impaired proliferation and invasion of trophoblast cells under hypoxia. This suggests that decreased expression of PAX3 is closely related to PE pathogenesis [3]. Previous studies have used high-throughput genomic and epigenomic technologies to identify higher methylation levels in the promoter region of PAX3 gene in the placenta of PE patients, which has provided an important clue for elucidating the down-regulation mechanism of PAX3 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly the presence of PAX3-FOXO1 promoted more robust changes in miRNA expression at 30 minutes with 72/82 miRNA (89%) having ≥1.3-fold increases or decreases in expression, with nearly half of these miRNA changing over 2.5-fold (Figure 2 ). The results described here are part of a larger genomics study and as such the observed changes in miRNA expression were previously validated by qRT-PCR and published by us [ 19 , 20 ].…”
Section: Resultssupporting
confidence: 68%
“…The transduced cells were selected with puromycin; selected cells were harvested from three independent transductions and pooled, resulting in a single mixed population for each individual construct, which removes the potential for variability that may occur from clonal effects. The observed level of PAX3-FOXO1 expression is equivalent to that of the fusion protein in ARMS tumor cell lines [ 19 , 20 ] and is therefore directly relevant to the role of the oncogenic fusion protein in ARMS.…”
Section: Resultsmentioning
confidence: 99%